Socialization of Emotional Literacy and Crime Prevention in Adolescents at Cahaya Bangsa Christian Junior High School, Tuapeijat Village - Asnur, Lise; Fransiska, Cyintia; Kurniawan, Farhan; Yosvita, Nadila; Yolanda, Nessa (Journal of English Language and Education, 2025)
This socialization of emotional literacy and crime prevention in adolescents was carried out at Cahaya Bangsa Christian Junior High School, Tuapeijat Village, Mentawai Islands Regency, by students of the Real Work Lecture (KKN) of Padang State University in 2025. The purpose of this activity is to increase adolescents' awareness and ability to recognize, understand, and manage emotions, as well as prevent their involvement in acts of violence or deviant behavior. The activity was attended by 60 students of grades VII and VIII with a duration of one full day. The method of the activity includes the delivery of interactive materials, group discussions, and emotional control simulations. The results of the activity showed that most students were not able to control their emotions well, especially when facing social pressure and conflicts between friends. After socialization, students show increased understanding of how to manage emotions and realize the importance of positive communication to prevent negative actions. Thus, this activity is effective in increasing emotional literacy and legal awareness in adolescents in the school environment.